2004
DOI: 10.2135/cropsci2004.2054
|View full text |Cite
|
Sign up to set email alerts
|

Semigamy Gene Is Associated with Chlorophyll Reduction in Cotton

Abstract: currently the only feasible means for production of haploids in cotton is via semigamy. Haploids produced by semigamy can be used to facilitate selectionSemigamy is a type of facultative apomixis in which in cotton (Gossypium barbadense L.) breeding and gene mapping. The the male sperm nucleus does not fuse with the egg objectives of the present study were to detail the genetic mechanism of nucleus after penetrating the egg in the embryo sac. Subsemigamy and its relationship with reduction in chlorophyll conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 20 publications
1
14
0
3
Order By: Relevance
“…Mapping populations are obtained using two contrasting parents for the desired trait. In self-pollinated crops; usually mapping populations include F 2 [56,57]; F 2:3 [58,59], recombinant inbred lines (RILs) [60,61], backcross (BC) [62,63], Backcross inbred lines (BILs) [64], near isogenic lines [65,66], doublehaploids [67,68], chromosome substitution lines (CSILs) [69,70]. F 2 , BC, RILs and doublehaploids have been highly used for linkage mapping studies in cotton.…”
Section: Mapping Populationmentioning
confidence: 99%
“…Mapping populations are obtained using two contrasting parents for the desired trait. In self-pollinated crops; usually mapping populations include F 2 [56,57]; F 2:3 [58,59], recombinant inbred lines (RILs) [60,61], backcross (BC) [62,63], Backcross inbred lines (BILs) [64], near isogenic lines [65,66], doublehaploids [67,68], chromosome substitution lines (CSILs) [69,70]. F 2 , BC, RILs and doublehaploids have been highly used for linkage mapping studies in cotton.…”
Section: Mapping Populationmentioning
confidence: 99%
“…Subsequent breeding and genetic experiments revealed that semigamy was an inheritable trait and controlled by a single incompletely dominant gene, denoted Se [7,8]. A unique feature of semigamy in cotton is that expression of the trait in terms of haploid production is controlled by the genotype of both male and female gametes [8].…”
Section: Introductionmentioning
confidence: 99%
“…In cotton, semigamy was first observed by Turcotte and Feaster [ 5 ] through recovery of a doubled haploid mutant 57-4 from a commercial non-semigametic Pima S-1, which produced haploids at a high frequency, ranging from 25 to 61% when self pollinated. Subsequent breeding and genetic experiments revealed that semigamy was an inheritable trait and controlled by a single incompletely dominant gene, denoted Se [ 7 , 8 ]. A unique feature of semigamy in cotton is that expression of the trait in terms of haploid production is controlled by the genotype of both male and female gametes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors proposed that the complementary function could be due to a non‐diploidized function of homoeologous loci in the G. hirsutum allotetraploid. Zhang and Stewart (2004) identified a gene responsible for lower chlorophyll content and photosynthetic rate of a semigamy mutant compared to the wild‐type, and suggested this gene could be either the same or closely linked with the semigamy gene ( Se ).…”
mentioning
confidence: 99%